High energy requirements and water throughput of adult Shuar forager‐horticulturalists of Amazonian Ecuador. Issue 2 (23rd February 2019) - Christopher, Lauren; Madimenos, Felicia C.; Bribiescas, Richard G.; Urlacher, Samuel S.; Snodgrass, James J.; Sugiyama, Lawrence S.; Pontzer, Herman
Abstract: Objectives: We measured total energy expenditure (TEE; kcal/d) and water throughput (L/d) among Shuar forager‐horticulturalists from Amazonian Ecuador to compare their daily energy and water demands to adults in other small‐scale and industrialized populations. Methods: TEE and water throughput were measured using the doubly labeled water method among 15 Shuar adults (eight women, seven men; age range 18‐60 years) living in a relatively remote village. We used multiple regression to assess the effects of anthropometric variables (body size, fat free mass, age, and sex) on TEE and water throughput. We also compared Shuar TEE and water throughput to those of other small‐scale and industrialized societies. Results: TEE among Shuar adults (men: 4141 ± 645 kcal/d, women: 2536 ± 281 kcal/d) was most strongly correlated with fat free mass. Estimated physical activity levels (PAL) calculated as (TEE/estimated BMR), were greater for men (2.34 ± 0.29) than women (1.83 ± 0.14, P  < 0.001). Water throughput was also greater among Shuar men (9.37 ± 2.34 L/d) than women (4.76 ± 0.36 L/d, P  < 0.001). Shuar TEE and water throughput were elevated compared to adults in industrialized populations. Discussion: TEE and PAL of Shuar men are among the highest recorded during normal daily life, and likely reflect both high levels of physical activity and cultural dietary practices. Drinking large amounts of chicha, a traditional carbohydrate‐rich drink made from manioc, likely contributes to the high levels of water throughput among Shuar men, and may contribute to elevated TEE.